Local environmental quality and interjurisdictional spillovers - Hatfield, John William; Kosec, Katrina (John Wiley & Sons, 2019)
We investigate how the quality of environmental public goods varies with the number of local governments, and show how this relationship depends on the existence of spillovers across jurisdictions. Exploiting exogenous variation in the natural topography of the USA, we show that metropolitan areas with more local governments have significantly lower air quality and significantly higher concentrations of toxic air pollutants that cause cancer and respiratory disease. By contrast, drinking water quality—a public good with relatively few spillovers—does not vary with the number of governments. Further, we find that areas with more local governments tend to have a higher density of employment in heavily polluting industries like electric power generation and chemical manufacturing, even after controlling for population density. This is consistent with jurisdictional fragmentation leading to the presence of more polluting industries.